IMPLEMENTASI LAYANAN OTOMASI USAHA LAUNDRI BERBASIS WORKFLOW AUTOMATION MENGGUNAKAN N8N - Al Fajar, Muhammad Arya; Gunawan; Wiradarma, Arga (AnoaTIK: Jurnal Teknologi Informasi dan Komputer, 2026)
The rapid development of information technology has encouraged the digitalization of business processes in Micro, Small, and Medium Enterprises (MSMEs), including laundry businesses. However, order management, service status tracking, and customer communication are still often performed manually, resulting in inefficiencies. This study aims to design and implement a laundry ordering and status tracking system based on workflow automation using the n8n platform integrated with a WhatsApp chatbot and real-time notifications. This research employed the Research and Development (R&D) method, which includes requirements analysis, system design, development, testing, implementation, and evaluation. The system was developed using Django as the backend framework, MySQL as the database, and n8n as the workflow automation engine. System integration was carried out through APIs connected to a Gemini AI-based WhatsApp chatbot. The results show that the system successfully automates communication and laundry status tracking through a WhatsApp chatbot and real-time notifications. Based on Black Box Testing, all major system features functioned according to the specified requirements without significant errors. The developed system improves the efficiency of information delivery to customers and supports more effective laundry business operations.